Alternative Approaches in Conflict Resolution (Rethinking Peace and Conflict Studies, 2018)
This edited volume brings together alternative and innovative approaches in conflict resolution. With traditional military intervention repeatedly leading to the transformation of entire regions into zones of instability and violence (Afghanistan, Iraq, Libya, Syria), the study of alternative and less violent approaches to conflict resolution has become imperative. Four approaches are presented here: negotiation, religion and gender, reconciliation and forgiveness, and the arts. This volume contains the insights and experiences of fourteen internationally renowned scholars and practitioners from different contexts. Can forgiveness help heal relationships in post-apartheid South Africa? How can art assist dealing with 'unrememberable' events such as the genocide in Rwanda? What transformational resources do women offer in contexts of massive human rights violations? The aim here is twofold: to provide and encourage critical reflection of the approaches presented here and to explore concrete improvements in conflict resolution strategies. In its interdisciplinary and international outlook, this work combines the tried-and-tested approaches from conflict resolution experts in academia, NGOs and civil society, making it an invaluable tool for academics and practitioners alike.